Children Object or Subject of Social Capital Formation Process? - Karaperyan, Tatevik (Journal of Sociology: Bulletin of Yerevan University, 2018)
Existing studies of social capital traditionally view children as objects and passive actors of the capital formation process. Acknowledging the child as an independent entity (subject) is a relatively new approach based on viewing them as subjects of rights. Here the child is an active participant of the social interaction process, who initiates in and develops their own social network. This article attempts to conducta comparative analysis of the two approaches mentioned above.
Keywords: social capital, childhood, social interactions, sociology of childhood, object, subject, socialization